2023
DOI: 10.1002/ijc.34626
|View full text |Cite
|
Sign up to set email alerts
|

ERα/LKB1 complex upregulates E‐cadherin expression and stimulates breast cancer growth and progression upon adiponectin exposure

Abstract: Adiponectin is the major adipocytes‐secreted protein involved in obesity‐related breast cancer growth and progression. We proved that adiponectin promotes proliferation in ERα‐positive breast cancer cells, through ERα transactivation and the recruitment of LKB1 as ERα‐coactivator. Here, we showed that adiponectin‐mediated ERα transactivation enhances E‐cadherin expression. Thus, we investigated the molecular mechanism through which ERα/LKB1 complex may modulate the expression of E‐cadherin, influencing tumor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
(163 reference statements)
1
0
0
Order By: Relevance
“…In line with our results, Naimo G.P. et al, 2023, showed that exposure to adiponectin increases E-cadherin at both mRNA and protein levels, promoting tumor growth and progression in ERα-positive breast cancer cells [ 32 ]. Moreover, it was shown that the expression of E-cadherin is essential for the anchorage-independent growth of oral squamous cancer cells [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…In line with our results, Naimo G.P. et al, 2023, showed that exposure to adiponectin increases E-cadherin at both mRNA and protein levels, promoting tumor growth and progression in ERα-positive breast cancer cells [ 32 ]. Moreover, it was shown that the expression of E-cadherin is essential for the anchorage-independent growth of oral squamous cancer cells [ 33 ].…”
Section: Discussionsupporting
confidence: 91%